x+x+x-6=48

Simple and best practice solution for x+x+x-6=48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+x+x-6=48 equation:


Simplifying
x + x + x + -6 = 48

Reorder the terms:
-6 + x + x + x = 48

Combine like terms: x + x = 2x
-6 + 2x + x = 48

Combine like terms: 2x + x = 3x
-6 + 3x = 48

Solving
-6 + 3x = 48

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 3x = 48 + 6

Combine like terms: -6 + 6 = 0
0 + 3x = 48 + 6
3x = 48 + 6

Combine like terms: 48 + 6 = 54
3x = 54

Divide each side by '3'.
x = 18

Simplifying
x = 18

See similar equations:

| (4x-3y)(2x+y)= | | .7x+1.5=3.88 | | 17s=459 | | 5/16=3/a | | 4x-7(3x-5)=4-3(4x-7) | | (n+12)-14=5n | | (4x-y)(2x-Y)= | | 5x+31=-53-9x | | x*6-4=-40 | | (4x+3Y)(2x+y)= | | 4(x-1)+2(x-7)=127 | | 91-I=72 | | Q(x)=3x-x+3 | | (4x+3y)(4x+y)= | | AB-3=BC-2 | | x-7.4=-5.1 | | 1.6+.6Y+2=.4Y | | (4x-y)(2x+3y)= | | (4x+y)(2x-3y)= | | 1.6+.6Y+2=9 | | 7h-45=46 | | 9-5n+1=21 | | r+31=16 | | 7m-24=25 | | Ab-3=bf-2d | | 8x^3-8x^2+32x-32=0 | | r+3=16 | | 36-4p= | | 9=m+16 | | 8.7=3.6+.6Y | | 3x+4y-2z=20 | | 6.8=3.6+.6Y |

Equations solver categories